2000
DOI: 10.1097/00000658-200006000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Hepatic Injury: A Paradigm Shift From Operative to Nonoperative Management in the 1990s

Abstract: ObjectiveTo analyze the outcome of hemodynamically stable patients with blunt hepatic injury managed nonoperatively, and to examine the impact of this approach on the outcome of all patients with blunt hepatic injury. Summary Background DataUntil recently, operative management has been the standard for liver injury. A prospective trial from the authors' institution had shown that nonoperative management could safely be applied to hemodynamically stable patients with blunt hepatic injury. The present study revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
210
4
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(239 citation statements)
references
References 22 publications
14
210
4
11
Order By: Relevance
“…The most common mechanism of liver injury in our study was blunt trauma (94 %) due to road traffic injuries among all age groups, which is much higher than reported in published literature [3,4]. Petrowsky et al [4] had reported 84 % incidence of blunt liver injury while Malhotra et al [3] had shown 82 % incidence of blunt liver trauma due to road traffic injuries.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…The most common mechanism of liver injury in our study was blunt trauma (94 %) due to road traffic injuries among all age groups, which is much higher than reported in published literature [3,4]. Petrowsky et al [4] had reported 84 % incidence of blunt liver injury while Malhotra et al [3] had shown 82 % incidence of blunt liver trauma due to road traffic injuries.…”
Section: Discussioncontrasting
confidence: 42%
“…The incidence of liver injury in our study is higher as compared to reported incidence of liver injury in literature. Croce et al [2] reported 5 % incidence of liver injury while Malhotra et al [3] had reported 4.6 % incidence of liver injury.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In most cases, treatment of injuries has shifted from early surgical treatment to NOM. NOM of blunt abdominal injuries is well established and strategies based on hemodynamic stability and CT scan findings are now widely used in the treatment of solid organ injuries [3][4][5].…”
mentioning
confidence: 99%
“…Over the past three decades multiple studies have shown that NOM of solid organ injuries is effective, with a reported success rate of more than 90% [3][4][5].…”
mentioning
confidence: 99%